First observation of the decay Bc+to → J/ψ K+ - Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2013)
The decay Bc+to → J/ψ K+ is observed for the first time using a data sample, corresponding to an integrated luminosity of 1.0 fb-1, collected by the LHCb experiment in pp collisions at a centre-of-mass energy of 7 TeV. A yield of 46 ± 12 events is reported, with a significance of 5.0 standard deviations. The ratio of the branching fraction of Bc+to → J/ψ K+ to that of Bc+to → J/ψ K+ is measured to be 0.069 ± 0.019 ± 0.005, where the first uncertainty is statistical and the second is systematic. © 2013 Cern for the benefit of the LHCb collaboration.